Quadrature Operation Point Locked Techniques for Interrogating Extrinsic Fabry‐Perot Interferometric Sensors. Issue 9 (27th June 2013) - Shang‐hui, Xiao; Yi, Jiang; Da, Liu; Jun, Tang
ABSTRACT A quadrature operation point locked technique for interrogating extrinsic Fabry‐Perot interferometric (EFPI) sensors is experimentally demonstrated. The voltage of quadrature operation point is set as the reference, and the output signal from the EFPI is filtered and compared with the reference. The difference voltage is used to shift the wavelength of the laser by changing the operation temperature. Experimental results show that the interrogation system can be locked at the quadrature operation point within a temperature range of 50°C. A linear output is realized when the system is locked. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2117–2120, 2013